2003
DOI: 10.1300/j020v21n04_04
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Trauma, Avoidance Coping, and Alcohol and Other Drug Use Among Women in Residential and Outpatient Treatment Programs

Abstract: This study evaluates the different types of childhood trauma, avoidance coping, and patterns of drug and alcohol use among 112 alcohol and drug abusing females in outpatient and residential treatment. A passive research design with self-report surveys was administered to female participants during treatment to assess the relationship between childhood trauma, coping methods, and alcohol and drug use. A multiple regression analysis demonstrated that women with a history of emotional abuse were more likely to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 20 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…Specifically, previous research has documented that CSA survivors are more likely to rely on avoidant coping strategies in response to distress (Fortier et al, 2009; Rosenthal, Rasmussen Hall, Palm, Batten, & Follette, 2005). Other researchers report that a history of diverse forms of childhood maltreatment (e.g., childhood physical and emotional abuse) results in increased reliance on avoidance-based coping (Gratz et al, 2007; Simons, Ducette, Kirby, Stahler, & Shipley, 2003). …”
Section: Outcomes Following Victimization: Distress and Strategies Fomentioning
confidence: 99%
“…Specifically, previous research has documented that CSA survivors are more likely to rely on avoidant coping strategies in response to distress (Fortier et al, 2009; Rosenthal, Rasmussen Hall, Palm, Batten, & Follette, 2005). Other researchers report that a history of diverse forms of childhood maltreatment (e.g., childhood physical and emotional abuse) results in increased reliance on avoidance-based coping (Gratz et al, 2007; Simons, Ducette, Kirby, Stahler, & Shipley, 2003). …”
Section: Outcomes Following Victimization: Distress and Strategies Fomentioning
confidence: 99%
“…Child-focused research indicates a positive association between experiential control and neuroticism (a construct related to anxiety). For example, results of two investigations showed that high levels of cognitive and emotional avoidance mediated the relationship between childhood abuse and poor outcomes in adulthood, including psychological distress and substance use (Simons, Ducette, Kirby, Stahler, & Shipley, 2003). In a study specific to childhood anxiety, Dempsey and colleagues found that denial and mental distraction predicted posttraumatic stress symptoms among inner-city youth exposed to high levels of violence.…”
Section: Costs Of Experiential Control In Childhood and Adolescencementioning
confidence: 99%
“…Kilpatrick and colleagues () reported that drug use was related to a higher number of childhood sexual and physical abuse experiences compared with alcohol use. In a sample of women suffering from substance use disorders and comorbid posttraumatic stress disorder (Simons et al., ), current drug use was related to childhood physical, sexual, and emotional abuse, whereas current alcohol use was unrelated to childhood abuse. According to these results, patients with alcohol dependence may show different childhood trauma profiles than patients with illicit drug dependence.…”
mentioning
confidence: 99%